PENGARUH MEDIA SOSIAL DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN HP IPHONE SECOND DI MARKETPLACE FACEBOOK (STUDI KASUS MAHASISWA UMB) - Prasetya, Onky Dwie; Herfianti, Meiffa (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to analyze the influence of social media and brand trust on the purchasing decisions of second-hand mobile phones (HP)Iphone  on the Facebook marketplace. The sampling method used in this research was proportional area random sampling. The study was conducted using a descriptive quantitative approach and involved a total of 69 respondents. Data were collected through the distribution of questionnaires. Data analysis was carried out using instrument testing, classical assumption testing, multiple linear regression analysis, the coefficient of determination (R²), and hypothesis testing (t-test). The results of the t-test for the social media variable showed that t calculated > t table (4.252 > 1.667) and sig (0.00 < 0.05). For the brand trust variable, the t-test also showed a significant result, with t calculated > t table (3.679 > 1.667). The results of the F-test indicated that the F calculated = 47.508 > F table = 3.13, and the significance value was 0.00 < 0.05. From these findings, it can be concluded that social media and brand trust have a significant and simultaneous influence on the purchasing decisions of second-hand mobile phones on the Facebook marketplace.   Keywords: Social Media, Brand Trust, Purchase Decision